+0  
 
0
403
8
avatar+93301 

This question was by Hadjer2015

But it didn't post properly so I am doing it here.  

 

please help me

$$\int$$(1-cos(x/3))/sin(x/2)

$$\int( x^{2}) /((x^2+3)(x+1))$$

 

[address of original question]

http://web2.0calc.com/questions/nbsp_20

Melody  Mar 22, 2015

Best Answer 

 #8
avatar+26971 
+5

I looked for a way to get the sin and cos terms the "same" in some sense, and I could see that if we had integer multiples of some common angle we could expand the result to get both in terms of the one angle.  

 

There might well be a more straightforward way of doing the integral!

.

Alan  Mar 22, 2015
 #1
avatar+93301 
+5

 

$$\\\displaystyle\int \frac{x^2}{(x^2+3)(x+1)}\;dx\\\\
Let \\
\frac{x^2}{(x^2+3)(x+1)}=\frac{Ax+B}{x^2+3}+\frac{C}{x+1}\\\\
\frac{x^2}{(x^2+3)(x+1)}=\frac{(Ax+B)(x+1)}{(x^2+3)(x+1)}+\frac{C(x^2+3)}{(x^2+3)(x+1)}\\\\
so\\
(Ax+B)(x+1)+C(x^2+3)=x^2\\\\
Ax^2+Ax+Bx+B+Cx^2+3C=x^2\\\\
(A+C)x^2+(A+B)x+(B+3C)=x^2\\\\$$

 

$$\\so\\
A+C=1 \;(1)\;\rightarrow \\
A+B=0\;(2)\; \rightarrow \\
B+3C=0\;\; \rightarrow\;\;B=-3C\;\; (3) \;\;$sub into (2)$\\
A-3C=0 (4)\\
(1)-(4)\\
4C=1\\
C=\frac{1}{4}=0.25 \\
A=1-0.25=0.75\\
B=-3*0.25=-0.75\\\\$$

 

$$\\so\\
\frac{x^2}{(x^2+3)(x+1)}=\frac{(0.75x-0.75)(x+1)}{(x^2+3)(x+1)}+\frac{0.25(x^2+3)}{(x^2+3)(x+1)}\\\\
\frac{x^2}{(x^2+3)(x+1)}=\frac{(0.75x-0.75)}{(x^2+3)}+\frac{0.25}{(x+1)}\\\\
\frac{x^2}{(x^2+3)(x+1)}=\frac{0.75x}{(x^2+3)}-\frac{0.75}{(x^2+3)}+\frac{0.25}{(x+1)}\\\\
\frac{x^2}{(x^2+3)(x+1)}=\frac{0.375*2x}{(x^2+3)}-\frac{0.75}{(x^2+3)}+\frac{0.25}{(x+1)}\\\\\\
\displaystyle\int\;\frac{x^2}{(x^2+3)(x+1)}\;dx\\\\\\
=\displaystyle\int\;\frac{0.375*2x}{(x^2+3)}\;dx-\displaystyle\int\;\frac{0.75}{(x^2+3)}\;dx+\displaystyle\int\;\frac{0.25}{(x+1)}\;dx\\\\\\
=0.375\;ln(x^2+3)+0.35\;ln(x+1)-\displaystyle\int\;\frac{0.75}{(x^2+3)}\;dx\\\\\\
$ Now I don't know what to do. BUMMER!$$$

 

I guess I wasn't meant to do it that way afterall.      LOL

Melody  Mar 22, 2015
 #2
avatar+88839 
+5

Melody....for that last integral.....let u = x , a = √3,   du = dx,  and we have the form.....

-0.75 ∫ 1 / [ u^2 + a^2] du  =

-0.75 [ tan-1 (u/a)] / a  + C  =

-.0.75 [tan -1 (x / √3)] / √3 + C

 

  

CPhill  Mar 22, 2015
 #3
avatar+93301 
0

Thanks Chris, I should have recognised that. :)

Melody  Mar 22, 2015
 #4
avatar+88839 
+5

Well...you got most of the difficult part done with the partial fraction stuff....!!!!

That's worth at least 3 points.........

P.S.  - I don't want to appear as though I'm a genius.....I went to the integral tables to find the proper form for that last part.....LOL!!!

 

  

CPhill  Mar 22, 2015
 #5
avatar+26971 
+5

For the first integral:

 

 integral pt1

integral pt2

This should be carefully checked as I tend to be a little cavalier with constants sometimes!

.

Alan  Mar 22, 2015
 #6
avatar+93301 
0

Thanks Alan. :)

Melody  Mar 22, 2015
 #7
avatar+88839 
0

Nice "double-substitution,"  Alan.

P.S -  How did it occur to you to let cos(x/3)  = cos(2Θ)   and sin(x/ 2) = sin(3Θ)  ???

  

CPhill  Mar 22, 2015
 #8
avatar+26971 
+5
Best Answer

I looked for a way to get the sin and cos terms the "same" in some sense, and I could see that if we had integer multiples of some common angle we could expand the result to get both in terms of the one angle.  

 

There might well be a more straightforward way of doing the integral!

.

Alan  Mar 22, 2015

5 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.